Chronic GPER1 Activation Protects Against Oxidative Stress-Induced Cardiomyoblast Death via Preservation of Mitochondrial Integrity and Deactivation of Mammalian Sterile-20-Like Kinase/Yes-Associated Protein Pathway - Imam Aliagan, Abdulhafiz; Madungwe, Ngonidzashe B.; Tombo, Nathalie; Feng, Yansheng; Bopassa, Jean C. (Frontiers in Endocrinology, 2020)
We recently reported that acute application of E2 at the onset of reperfusion in vivo induces cardioprotective effects against I/R injury via activation of its non-steroidal receptor, G protein-coupled estrogen receptor 1 (GPER1). Here, we investigated the impact and mechanism underlying chronic GPER1 activation in cultured H9c2 rat cardiomyoblasts. H9c2 rat cardiomyoblasts were pre-treated with the cytotoxic agent H2O2 for 24 hours and incubated in the presence of vehicle (control), GPER1 agonists E2 and G1, or GPER1 agonists supplemented with G15 (GPER1 antagonist) for 48 or 96 hours. After treatment, cells were collected to measure the rate of cell death and viability using flow cytometry and Calcein AM assay or MTT assay. The resistance to opening of the mitochondrial permeability transition pore (mPTP), the mitochondrial membrane potential and ATP production were assessed using fluorescence microscopy, and the mitochondrial integrity was observed with electron microscopy. The levels of the phosphorylation of mammalian sterile-20-like kinase (MST1) and yes-associated protein (YAP) were assessed by Western blot analysis, while the expression levels of mitochondrial biogenesis genes, YAP target genes, and pro-apoptotic genes were measured by qRT-PCR. We found that after H2O2 treatment, chronic E2/G1 treatment decreased cell death effect was associated with the prevention of the S phase of the cell cycle arrest compared to control. In mitochondria, chronic E2/G1 activation treatment preserved the cristae morphology, and increased resistance to opening of mPTP, but with little change to mitochondrial fusion/fission. Additionally, chronic E2/G1 treatment reduced phosphorylation of MST1 and YAP, and increased MST1 and YAP protein levels. E2 treatment also up-regulated the expression levels of TGF-β and PGC-1α mRNAs and down-regulated PUMA and Bim mRNAs. Except for ATP production, all the E2/G1 effects were prevented by the co-treatment with G15. Together, these results indicate that chronic GPER1 activation protects H9c2 cardiomyoblasts against oxidative stress-induced cell death and increases cell viability by preserving mitochondrial structure and function as well as delaying the opening of mPTP. These chronic GPER1 effects are associated with the deactivation of the non-canonical MST1/YAP mechanism that leads to genetic upregulation of cell growth genes, and downregulation of pro-apoptotic genes.